The Fruit and Vegetable Carving : Value-Added to Thai Food: Fruit and Vegetable Carving : Value-Added to Thai Food - hongrattanavorakit, sakarin (Journal of Thai Food Culture, 2023)
Fruit and vegetable carving is a cultural wisdom, using concentration, meticulousness, creativity, and practice. The carving represents Thai identity which reflects social and cultural development with combination of local fruits and vegetables and local knowledge from generations to generations to adapt with ways of life and society. Then it was developed to be personal profession and become a technician. This article analyzed vegetable and fruit carving : value-added to Thai food and found that the adaptation of vegetable and fruit carving is considered a s a kind of creative art of food, reflecting to intention to decorate and well meticulous cook. In addition, it helped impress customers. Applying fruit and vegetable carving to add value to Thai food created identity in food services such as food stalls and restaurants in places. In addition, Thai fruit and vegetable decoration spreads to other nations. It is considered as cultural spread in another way.